PENGARUH VARIABEL BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA PERUSAHAAN DAERAH AIR MINUM (PDAM) WILAYAH JAWA-BALI - Utomo, Agus (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2010)
This research is done of PDAM Java-Bali region, concerning to the title of the Influence Analysis of culture toward job satisfaction and corporate performance.The amount if samples in this research is about 324 Directors of PDAM Java-Bali Area, by its analysis unit on the organizational level of PDAM cover the 3 directors : Prime director, General Director and Technical director of 114 offices of PDAM. Data is collected by using media questionnaire. Technique of Analysis used in this research is based on structured Equation Modelling by using AMOS 6th version software.The result shows the findings of : The Organization values have positive and significant influences toward the job satisfaction; The organization climate has positive and significant influences toward the job satisfaction; The attention to detail has a positive but not significant influence toward the job satisfaction: The outcome orientation has a positive but not significant influences toward the job satisfaction; The teamÂ  orientation has negative and non significant influences toward the job satisfaction; The aggressiveness has positive and significant influences toward the job satisfaction; The organization values have positive and significant influences toward the corporate performance The Organization Climate has negative and non significant influences toward the corporate performance; The attention to detail has positive and not significant influences toward the corporate performances.The team orientation has negative and non significant influences toward the corporate performance; the aggressiveness has positive and significant influences toward the corporate performance; job satisfaction has positive and significant influences toward the corporate performance. The result of this research also performs that over the job satisfaction, the organization values, organization climate, and aggressiveness have positive and significant influences toward the corporate performance.These specific findings could be contributed to the development of corporate culture in order to increase the PDAM Job Satisfaction and Performance. Itâ€™s, therefore, the time to adopt and more pushing the organization values, organization. Climate and aggressiveness, as they become the corporate culture variables that fully supported to everybody among individual organization and society using the PDAM product.Keywords : Corporate Culture, Job Satisfaction and Corporate Performance.